1-4 SINF JISMONIY TARBIYA DARSLARIDA O‘QUVCHILARNING KOORDINATSION QOBILIYATLARINI RIVOJLANTIRISHDA TA’SIR ETUVCHI OMILLAR - Ruzmetov, N.K. (SCIENCE and SOCIETY, 2019)
The article deals with the description of specific exercises and guidelines for developing coordination skills for pupils of the 1-4 forms at physical education classes.
Keywords: coordination; special exercise; development; primary school; principle; abilities